Serological evidence of West Nile Virus infection among humans in the southern Provinces of Morocco - Hicham El Rhaffouli; Idriss Lahlou-Amine; Chafiqua Loutfi; Abdellilah Laraqui; Tahar Bajjou; Ouafaa Fassi-Fihri; Mehdi El Harrak (Journal of Infection in Developing Countries)
Introduction: The objective of this study was to determine the prevalence of West Nile Virus infection in the southern provinces of Morocco. Methodology: A total of 250 sera, collected during 2012 in the province of Dakhla, were analyzed by microneutralisation assay. Results: WNV-neutralizing antibodies were detected in 13 samples (5.2%). The participants with WNV-specific antibodies were significantly younger than the rest of the population (p = 0.009). The positivity rate was higher among women (6.3%) than men (3.6%) (p = 0.26). Conclusions: This is the first serological evidence of WNV infection among humans in the southern provinces of Morocco.